Perencanaan Preventive Maintenance Pada Bengkel Mekanik SMKN 2 Pangkalpinang - Suryadi, Muhammad; Aswin, Fajar; Sukanto, Sukanto (Jurnal Inovasi Teknologi Terapan, 2023)
Preventive maintenance is an activity to maintain the condition of the machine that is carried out in a planned/scheduled manner. Preventive maintenance itself includes scheduling, implementation, and improvement/modification. The purpose of this research is to carry out preventive maintenance on machine tools to maintain optimal engine conditions, ensure machine availability and reduce maintenance costs to a minimum. The preventive maintenance system design method is based on machine condition data collected by observing related machines and interviewing informants at SMKN 2 Pangkalpinang. Data from observations and interviews were used to calculate and determine the value of machine complexity so that a lathe maintenance system was obtained in the form of preventive maintenance design schedule data, annual preventive maintenance schedules, work specifications, and control cards. The results showed that the recommended preventive maintenance system design was acceptable to be implemented on lathes at SMKN 2 Pangkalpinang within 2 years. Further research is needed to increase the effectiveness of this preventive maintenance system. Some things that need to be further developed include a system for managing materials and machine parts inventory and changing engine oil using the oil listed in the lubrication table.